Residential mobility, well-being, and mortality. [article]. - Oishi, Shigehiro
We tested the relation between residential mobility and well-being in a sample of 7,108 American adults who were followed for 10 years. The more residential moves participants had experienced as children, the lower the levels of well-being as adults. As predicted, however, the negative association between the number of residential moves and well-being was observed among introverts but not among extraverts. We further demonstrated that the negative association between residential mobility and well-being among introverts was explained by the relative lack of close social relationships. Finally, we found that introverts who had moved frequently as children are more likely to have died during the 10-year follow-up. Among extraverts, childhood residential mobility was unrelated to their mortality risk as adults. These findings indicate that residential moves can be a risk factor for introverts and the extra-version can be an interpersonal resource for social relationships and well-being in mobile societies.